Probability-Theoretical Models of Physical Random Number Generators - Bogdanov, D. S.; Logachev, A. S.; Mironkin, V. O. (Automatic control and computer sciences, 2024)
— This article presents the main probability-theoretic models that describe a wide class of physical random number generators and allow us to propose general approaches to their synthesis and analysis.